Kinerja dan Perbaikan Sistim Produksi Peternakan Sapi Potong Berbasis Kelompok di Pedesaan - Akhmad Sodiq; Nur Hidayat (Jurnal Agripet, 2014)
(Performance and improving beef cattle production system of farmer group based in the rural areas)ABSTRACT. The objectives of this study was to determine the performance of beef cattle farm under improved production systems of farmer group in the rural areas. Data were collected from 20 beef cattle farmer groups located in Cilacap, Banyumas, Banjarnegara and Kebumen regencies. Intervension factors such as improved production system including aspects of institutional, banking access, diversification of business, trading, and development programs. Regular reporting, interviews, field observations, and forum group discussion were implemented. Descriptive analysis was applied in this study. Variables focused on livestock production systems improvement, type and performance of development program, social resource potential and group dynamics, productivity levels, and also proposed program and recommendations of action programs. This study revealed that 10% of beef cattle farmer group implementing fattening cattle, and mostly (90%) applying combination of cow-calf operation and fattening. All of the beef cattle farmer group (100%) had a high score of social resources potential, while the group dynamics tend to stable (60%) and increased (40%). Mean of reproduction performance were 2.4 (S/C), 13.7 month (calving interval), and 76.5% (pregnancy rate). In general, BCS ranging from 4 to 7 with the highest score of 6 (45%) and followed by 7 (40%). Follow-up activities for recommendation of the action program could be the Beef Cattle Cluster Development of Farmer Group Based in the Rural Areas.